Evolution and aetiological shift of catheter‐related bloodstream infection in a whole institution: the microbiology department may act as a watchtower. (9th April 2013) - Rodríguez‐Créixems, M.; Muñoz, P.; Martín‐Rabadán, P.; Cercenado, E.; Guembe, M.; Bouza, E.
<x xml:space="preserve">Abstract</x> Clin Microbiol Infect Abstract The incidence of central‐line‐associated bloodstream infection (CLA‐BSI) is reported per 1000 days of catheter exposure, mainly in the intensive care unit (ICU), because recording exposure throughout an institution is not always feasible. Confirmation of catheter‐related bloodstream infection (CR‐BSI) requires specific laboratory testing that identifies the catheter as the source of infection. This information is available in microbiology laboratories and can be assessed using a denominator of 1000 admissions. We evaluated recent trends in the incidence and aetiology of CR‐BSI and compared adult ICUs with the remaining areas of the hospital in a retrospective cohort analysis of all confirmed CR‐BSIs. During the 8‐year study period, we recorded 1208 episodes (8.2% of BSIs) of CR‐BSI. After adjusting for the blood cultures drawn, a significant reduction in incidence was observed in adult ICUs (47%), where care bundles had been applied. The reduction was similar irrespective of whether CLA‐BSI or CR‐BSI was assessed. We recorded a significant reduction in the incidence of Staphylococcus aureus CR‐BSI, and a significant increase in the incidence of CR‐BSI caused by Enterococcus sp., Gram‐negative microorganisms and fungi. The microbiology department may complement CLA‐BSI/1000 catheter‐days by providing CR‐BSI when days of exposure are not available, because both figures are parallel. We demonstrated a significant reduction in the incidence of CR‐BSI in recent years in the population admitted to adult ICUs but not in the remaining areas of the hospital. A shift in the aetiological spectrum of CR‐BSI may be occurring.